1967
DOI: 10.1021/jf60154a032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental and biological factors on persistence of malathion applied as ultra-low-volume or emulsifiable concentrate to cotton plants

Abstract: A comparison of the persistence of malathion applied to cotton leaves as a water-diluted emulsifiable concentrate or as an ultra-low-volume formulation showed that the ULV persisted longer than the emulsifiable concentrate with a half-life value of 4.6 and 2 days, respectively. Studies with glass surfaces indicated that faster evaporation of the EC was, in part, responsible for the differential in persistence of the two formulations, particularly at 50= C. The EC formulation penetrated the leaf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, the rapid dissipation of originally applied pesticide are dependent on a variety of environmental factors such as sunlight and temperature [32]. However, high temperature is reported to the major factor in reducing the pesticides from plant surface [33]. Light plays an important role in the behavior of pesticide in the environment [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rapid dissipation of originally applied pesticide are dependent on a variety of environmental factors such as sunlight and temperature [32]. However, high temperature is reported to the major factor in reducing the pesticides from plant surface [33]. Light plays an important role in the behavior of pesticide in the environment [34].…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth particularly for fruits is also responsible to a great extent for decreasing the pesticide residue concentrations due to growth dilution effects [32] In addition, the rapid dissipation of originally applied pesticide are dependent on a variety of environmental factors such as sunlight and temperature [33]. However, high temperature is reported to the major factor in reducing the pesticides from plant surface [34]. Light plays an important role in the behavior of pesticide in the environment [35].…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding oxon was confirmed by GC analysis of com forage treated with emulsifiable concentrate formulation of (152) but its route of formation was ambiguous due to the harsh Soxhlet extraction (Bowman and Leuck 1971). Malathion (167) is considered to be also resistant to direct photolysis, and only hydrolysis of ester linkages is a dominant pathway (Awad et al 1967;EI-Refai and Hopkins 1972;Mostafa et al 1974). Metabolism of 14C_ and 32P-phenthoate (168) in Valencia orange leaves and fruit showed that the main degradation pathways on the surface were P=S oxidation to the oxon, stepwise hydrolysis at the S-C bond and carboxylate moiety to mandelic acid, and hydrolysis of the P-S bond followed by formation of disulfide (Takade et al 1976).…”
Section: Photodegradation Of Pesticides On Plantsmentioning
confidence: 98%
“…The volatilization loss was greatly reduced on silica gel, with the main product being the oxon (Mikami et al 1977b). Loss of (167) from the glass surface was mainly due to thermal vaporization (Awad et al 1967;El-Refai and Hopkins 1972). The basic photochemistry was almost the same for propaphos (159) either on glass or silica gel and was characterized by the significant formation of the S-oxidized derivatives (Fujii et al 1979).…”
Section: Photodegradation Of Pesticides On Glass and Silica Gel Sumentioning
confidence: 99%